Pharmacokinetics of fluorobenzyl polyethylene glycol conjugated tetraiodothyroacetic acid (NP751), a novel anticancer thyrointegrin αvβ3 antagonist - Fujioka, Kazutoshi; Hay, Bruce A.; Godugu, Kavitha; Mousa, Shaker A. (Frontiers in Pharmacology, 2022)
We have recently reported on the development of fb-PMT (NP751), a conjugate of the thyroid hormone metabolite tetraiodothyroacetic acid (tetrac) and monodisperse polyethylene glycol 36. It exhibited high affinity for thyrointegrin αvβ3 receptor and potent anti-angiogenic and anticancer activity in vivo. The objective of the current study is to determine the pharmacokinetics (PK) of fb-PMT in experimental animals, such as mice, rats, and monkeys. NP751 was quantified using a propylene diamine-modified tetraiodothyroacetic acid (DAT) as an internal standard. The limit of quantification (LOQ) for fb-PMT was 1.5 ng/μL and the recovery efficiency was 93.9 % with the developed method. The peak plasma concentration (Cmax) and the area under the curve (AUC) results at different doses in mice, rats and monkeys suggest that pharmacokinetics of NP751 is dose-dependent within the dose ranges administered. Results indicate that NP751 has comparable PK parameters that provides enough exposure as a molecularly tumor targeted molecule in multiple species and is a promising anticancer therapeutic.